Multi-organ pathology in a small porcine model of cytokine storm syndrome characteristics - Jin, Jiaqian; Fan, Linxiao; Chen, Richai; Lin, Xuanhao; Zhang, Sainan; Zhu, Mengfei (Frontiers in Immunology, 2025)
IntroductionCytokine Storm Syndrome (CSS) is a severe immune dysregulation characterized by excessive cytokine release and multi-organ injury. Existing murine models inadequately replicate human CSS. This study aimed to establish a D-galactosamine (D-GalN)-induced miniature pig model to investigate multi-organ pathological changes and inflammatory dynamics.MethodsTwenty-four male minipigs were divided into control and D-GalN groups (n=12 each). The experimental group received 1.5 g/kg D-GalN intravenously. At 0 h, 12 h, 24 h, and 36 h post-induction, tissues from the liver, lungs, intestines, heart, spleen, and kidneys were collected for hematoxylin-eosin (H&E) staining and IL-6 immunohistochemistry.ResultsHistopathology revealed progressive, time-dependent multi-organ injury. The liver, lungs, and intestines showed the earliest and most severe damage, including hepatocellular necrosis, alveolar congestion, and intestinal epithelial destruction. IL-6 expression increased over time, first peaking in the liver and later spreading to the lungs, intestines, and other organs. At 36 h, IL-6 was diffusely expressed in hepatic and pulmonary tissues, indicating an escalating systemic inflammatory response.DiscussionThis minipig CSS model replicates human-like disease progression and identifies the liver as a likely initiator of systemic inflammation. The observed “liver initiation–lung and intestine diffusion” pattern provides new insights into CSS pathogenesis. The temporal expression of IL-6 suggests a critical therapeutic window prior to 24 h post-onset for anti-inflammatory interventions, including artificial liver support and IL-6 blockade.